Presentation of preclinical gastrointestinal anatomy via laparoscopic simulation. Issue 7 (4th June 2022) - McCumber, Travis L.; Mott, Justin L.; Merani, Shaheed; Rochling, Fedja A.
Abstract: In this report, the authors examine the integration of teaching anatomical science with clinical implications in minimally invasive surgery. The authors hypothesized that implementation of integrated laparoscopic simulation during undergraduate medical education would improve student learning of anatomical structures from in situ, laparoscopic orientations; and subsequently improve student preparation for clinical rotations and clerkships. During the fall of 2020 and 2021, 260 (130 students/year) second year medical students at the University of Nebraska Medical Center participated in a six‐week gastrointestinal curriculum. Following a traditional anatomy dissection experience, students completed a laparoscopic event consisting of narrated laparoscopic videos and hands‐on laparoscopic simulation. To examine the integrated curricular event, outcome measures focused on technical performance using grasping forceps, anatomical knowledge, and perception of the educational innovation. Outcomes were analyzed via timed performance and a pre and post assessment that was designed to assess student anatomical knowledge and perception. Completion of the technical performance assessment ranged from 1 min, 17 s to 6 min. Student knowledge of anatomical structures from in situ, laparoscopic orientations following the laparoscopic simulation sessions was significantly improved (53.3% pre vs 81.0% post), and almost all students (98.9%) agreed that the simulation sessions improved their understanding of laparoscopic anatomy and procedures. This report demonstrates the implementation of a multidisciplinary, integrated simulation that satisfied basic science anatomy teaching objectives, while enhancing student enthusiasm for the content. Future studies will examine the subsequent impact of the innovation on student preparedness for clinical rotations and clerkships.